Original paperDEVELOPMENT AND EVALUATION OF A NOVEL TAEKWONDO CHEST PROTECTOR TO IMPROVE MOBILITY WHEN PERFORMING AXE KICKS - Woo, J.H; Ko, J.Y.; Choi, E.Y.; Her, J.G.; O’Sullivan, D.M. (Biology of Sport, 2013)
The axe kick, in Olympic style taekwondo, has been identified as the most popular scoring technique aimed to the head during full contact competition. The first purpose of this study was to identify and investigate design issues with the current World Taekwondo Federation approved chest protector. A secondary purpose was to develop a novel chest protector addressing the identified design issues and to conduct a biomechanical analysis. Fifteen male elite Taekwondo players were selected to perform three different styles of the axe kick, i.e., front, in-out, and out-in axe kick five times each for a total of 45 kicks. Two-way repeated measures ANOVA showed significant differences between the novel and existing chest protector conditions for vertical height of the toe, downward kicking foot speed, hip flexion angle and ipsilateral shoulder flexion extension range of motion (ROM) (p<0.05). There were no significant differences between the control condition (no chest protector) and the novel chest protector condition for these variables (p>0.05). These results indicate that the novel chest protector interferes less with both the lower and upper limbs during the performance of the axe kick and provides a more natural, free-moving alternative to the current equipment used.